ANALISIS EKONOMI USAHA PENANGKAPAN DAN PEMASARAN KEPITING BAKAU (Scylla serrata) DI DESA MUARA BADAK ILIR KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Maliang; Bambang Indratno Gunawan; Elly Purnamasari (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
The study aims to: (1) analyze estimated profit of mangrove crab fishery at Muara Badak Ilir Village, Muara Badak Subdistrict Kutai Kartanegara Regency; (2) determine marketing channel and efficiency of mangrove crab fishery in the studied area and (3) know main problems faced by crab fishermen related to the ban policy to the capture of mature female and the specified crab species in the area. Results showed that the estimated profit of crab fisher was Rp 7.920.607,14,- /month. In addition, the estimated profit achieved by crab middleman was calculated as Rp 9.682.444,44,-/month. Marketing institutions those involved in the crab business in the village level were fishermen, middlemen and local consumers while retailers, wholesaler, exporter and national and foreign consumers are the remaining institutions those run out of the village. Margin level both fisher and middleman was determined Rp 4.700 with the marketing efficiency level was 86% meaning that the crab market was efficient. The main problems found in the field were the following: the lack of information regarding the ban policy, fishermen faced the increased income due to this policy, the fishermen’sdilemma onthe utilization of the mature female crabs as the natural resources and the lack of policy dissemination to the coastal community concerning the capture ban of mature and the specified crabs. Key words: Economic Analysis, Fishery, Marketing, Mangrove Crab, Muara Badak Ilir